Cost Effectiveness of Insulin Glargine versus Neutral Protamin Hagedorn Insulin in the Treatment of Type 2 Diabetes Patients in Turkey - Ilhan Satman; Hayley Bennett; Candeger Yilmaz; Sazi Imamoglu; Goksun Ayvaz; Abdurrahman Comlekci; Demet Ozkaya; Toros Sahin (Journal of Health Economics and Outcomes Research)
**Background:** Type 2 diabetes mellitus (T2DM) poses a significant burden on population well being and healthcare expenditure in Turkey, with disease prevalence continuing to increase. Insulin treatment is necessary for patients failing to achieve glycaemic control with lifestyle modification or oral antidiabetic drugs. While neutral protamin Hagedorn (NPH) insulin has been traditionally prescribed for insulin introduction, insulin glargine has been shown to reduce glycated hemoglobin (HbA1c) with a more favourable hypoglycaemic profile.